Modalitas RA. Anita Noeringhati pada Pemilihan Dewan Perwakilan Rakyat Daerah Provinsi Sumatera Selatan 2019 - Rizki Maharani; Mudiyati Rahmatunnisa; Leo Agustino (Universitas Negeri Medan, 2020)
The purpose of this study was to find out, understand, and analyze the modalities that were RA. Anita Noeringhati's victory factor as a member of the Regional House of Representative of South Sumatra Province 2019. The method used is a qualitative research method with interviews and documentation data collection techniques. Based on the data obtained, the modalities that support RA. Anita Noeringhati's victory are, first, economic capital in the form of assets, and donations from the party. Second, social capital consists of social interaction with political elites, organizations and society, and forms of community trust. Third, cultural capital in the form of RA. Anita Noeringhati's ability to deal with the public. Fourth, symbolic capital in the form of political experience, and awards obtained by RA. Anita Noeringhati. The capital that plays the most role in RA. Anita Noeringhati's victory is the social capital that she has built for a long time.